Superalloys 1988 (Sixth International Symposium) 1988
DOI: 10.7449/1988/superalloys_1988_775_783
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Research on Transient Liquid Insert Metal Diffusion Bonding on Nickel Base Alloys

Abstract: This paper is concerned with the theoretical consideration on the transient liquid insert

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Thedetailed effects which occur during TLP brazing have recently been elucidated [1][2][3], and modelled [4,5]. Nakagawa et al [6-] employed one-dimensional finite difference modelling to analyse base metal dissolution behavior and isothermal solidification during TLP brazing of Ni-200 base metal, and emphasized the importance of filler metal thickness, and of heating rate between the filler metal melting temperature and the brazing temperature, on the dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…Thedetailed effects which occur during TLP brazing have recently been elucidated [1][2][3], and modelled [4,5]. Nakagawa et al [6-] employed one-dimensional finite difference modelling to analyse base metal dissolution behavior and isothermal solidification during TLP brazing of Ni-200 base metal, and emphasized the importance of filler metal thickness, and of heating rate between the filler metal melting temperature and the brazing temperature, on the dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent activation energies for isothermal solidification, which correspond to the activation energies for the diffusion of the melting point depressant (boron), are also shown in Table 2. The apparent activation energies for isothermal solidification of CMSX-2 single crystal are 266 kJ/mol (for MBF-80) and 248 kJ/mol (for F-24) and are slightly higher than those found for Ni base polycrystal superalloys (199-219 kJ/mol) [11]. It has been reported that isothermal solidification is controlled by the diffusion of boron into the base metal in Ni base polycrystal superalloys [11].…”
Section: Isothermal Solidification Processmentioning
confidence: 93%
“…The apparent activation energies for isothermal solidification of CMSX-2 single crystal are 266 kJ/mol (for MBF-80) and 248 kJ/mol (for F-24) and are slightly higher than those found for Ni base polycrystal superalloys (199-219 kJ/mol) [11]. It has been reported that isothermal solidification is controlled by the diffusion of boron into the base metal in Ni base polycrystal superalloys [11]. The activation energy value found when bonding CMSX-2 base metal would be determined by the diffusion of boron into the solid substrates.…”
Section: Isothermal Solidification Processmentioning
confidence: 95%
See 1 more Smart Citation
“…In the absence of ferrite, the high degree of segregation can also degrade corrosion resistance. A large amount of work has been conducted on high-energydensity (I-ED) welding of the 300 series stainless steels and this work has shown that alloy composition can have a large effect on weld structure and the development of unique microstructure [1][2][3][4][5][6][7][8][9]. In this study, the ability to develop unique structures, i.e.…”
Section: Introductionmentioning
confidence: 99%